Concordance of local guidelines with national guidelines on perioperative antibiotic and antiseptic prophylaxis in elective oral and maxillofacial surgery: A cross-sectional survey in the Netherlands - Teuntje Kamps; Mark Kregel; Saskia Kuipers; Tong Xi; Jaap ten Oever (Elsevier, 2021)
Local antibiotic guidelines should comply with national guidelines on perioperative antibiotic prophylaxis to adequately reduce surgical site infections in high-risk oral and maxillofacial (OMF) operations. To inform antibiotic committees on opportunities for improvement, a survey was sent to twenty-one OMF surgery departments in the Netherlands that performed more extensive OMF procedures. We determined (1) the local recommendations on perioperative antibiotic and antiseptic prophylaxis of sixteen elective OMF surgeries and (2) the local compliance with national guidelines. The response rate was 76.1%. Antibiotic prophylaxis was recommended in 78.8% of the OMF procedures and the regimens varied considerably between departments. Postoperative continuation of antibiotic prophylaxis was advised for 39.7% of the procedures and concerned 5-7 days in 81.0%. Antiseptic prophylaxis was recommended in 66.5% of the operations. The mean percentages of local recommendations that fully complied with the three national guidelines were 5.4% (range 0.0-55.6%) for the Dutch Working Party on Antibiotic Policy guideline, 27.7% (20.0-44.4%) for the 2018 guideline of the Dutch OMF Surgery Association (NVMKA) and 25.5% (16.7-44.4%) for the 2019 NVMKA guideline. In conclusion, deviation from national guidelines occurred frequently. Unification of the national guidelines in combination with guideline revisions are warranted, followed by better local implementation.